2018
DOI: 10.1177/2309499018802483
|View full text |Cite
|
Sign up to set email alerts
|

Results of tenorrhaphy with early rehabilitation for acute tear of Achilles tendon

Abstract: Background: For the treatment of acute Achilles tendon rupture, early rehabilitation after surgical repair is believed to be a useful method. The purpose of this study was to evaluate the outcome of open tenorrhaphy followed by early rehabilitation. Methods: A total of 112 patients who underwent open repair and early rehabilitation for acute Achilles tendon rupture from January 2003 to March 2015 were retrospectively reviewed. These 112 patients (80 men, 32 women) had an average age of 43.1 years (22-62 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…This evidence is due to the use of However accelerated protocol seems to provide positive aspects: first off all, according to Huang et al [19] faster mobility of the ankle joint produced a better restoration of articular range of motion, with an improvement of local edema and to prevent stiffness and calf atrophy [20]. Moreover in previous literature [21] Regarding clinical and functional outcomes, Ryu et al [22] reported a case series of 112 patients treated with early rehabilitation for acute tear of Achilles tendons. All patients included in this study were fully satisfied, with an AOFAS score at 1 year follow up of 95.7.…”
Section: Discussionmentioning
confidence: 96%
“…This evidence is due to the use of However accelerated protocol seems to provide positive aspects: first off all, according to Huang et al [19] faster mobility of the ankle joint produced a better restoration of articular range of motion, with an improvement of local edema and to prevent stiffness and calf atrophy [20]. Moreover in previous literature [21] Regarding clinical and functional outcomes, Ryu et al [22] reported a case series of 112 patients treated with early rehabilitation for acute tear of Achilles tendons. All patients included in this study were fully satisfied, with an AOFAS score at 1 year follow up of 95.7.…”
Section: Discussionmentioning
confidence: 96%
“…The reference sources report methodological discrepancies in the applied physiotherapy protocols for patients after the surgical suturing of the AT [46][47][48]. Physiotherapeutic procedures conducted up to 4 months after surgical suturing of the AT have already been described [49,50]. The applied postoperative protocol in this research included the types and number of exercises, series, and rest breaks [19].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 40 out of 81 patients (49%) with acute Achilles tendon ruptures were unable to perform a single heel raise at 12 weeks after the injury. In a study by Ryu et al, 41) 87 of 112 patients with acute Achilles tendon ruptures had difficulty with a single heel raise at 3 months after open tenorrhaphy followed by early rehabilitation; however, all patients were able to raise the heel 6 months postoperatively.…”
Section: Prognosismentioning
confidence: 98%
“…McCormack and Bovard 52) noted a 10% to 30% calf strength deficit on the injured side compared to the uninjured side in their patients with acute Achilles tendon tears. Ryu et al 41) also reported that even in patients who were able to perform single heel raises and sports after operative repair of acute tears and early rehabilitation, the calf circumference decreased by an average of 1.6 cm on the injured side and the isokinetic flexion peak torque deficit at 30°/sec was 16% (range, 0% to 21%) on the injured side compared with the uninjured side.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation